Neutralizing human antibodies prevent Zika virus replication and fetal disease in mice - Sapparapu, Gopal; Fernandez, Estefania; Kose, Nurgun; Bin Cao; Fox, Julie M.; Bombardi, Robin G.; Zhao, Haiyan; Nelson, Christopher A.; Bryan, Aubrey L.; Barnes, Trevor; Davidson, Edgar; Mysorekar, Indira U.; et al. (Nature (London), 2016)
Monoclonal Zika-virus-neutralizing human antibodies can protect against maternal–fetal transmission, infection and disease. Anti-Zika antibody blocks viral replication This paper reports the isolation of human monoclonal antibodies from the B cells of eight subjects who had recovered from Zika virus infection. The authors determine the immune specificity and epitope recognition patterns of the antibodies and demonstrate that one of the pan-ZIKV neutralizing antibodies, termed ZIKV-117, can protect mice both post-infection and pre-infection, and provide fetal protection in a pregnancy model. Zika virus (ZIKV) is an emerging mosquito-transmitted flavivirus that can cause severe disease, including congenital birth defects during pregnancy 1 . To develop candidate therapeutic agents against ZIKV, we isolated a panel of human monoclonal antibodies from subjects that were previously infected with ZIKV. We show that a subset of antibodies recognize diverse epitopes on the envelope (E) protein and exhibit potent neutralizing activity. One of the most inhibitory antibodies, ZIKV-117, broadly neutralized infection of ZIKV strains corresponding to African and Asian-American lineages. Epitope mapping studies revealed that ZIKV-117 recognized a unique quaternary epitope on the E protein dimer–dimer interface. We evaluated the therapeutic efficacy of ZIKV-117 in pregnant and non-pregnant mice. Monoclonal antibody treatment markedly reduced tissue pathology, placental and fetal infection, and mortality in mice. Thus, neutralizing human antibodies can protect against maternal–fetal transmission, infection and disease, and reveal important determinants for structure-based rational vaccine design efforts.